Endoscopic surgery in Japan: The 13th national survey (2014‐2015) by the Japan Society for Endoscopic Surgery. Issue 1 (25th January 2019) - Shiroshita, Hidefumi; Inomata, Masafumi; Bandoh, Toshio; Uchida, Hiroki; Akira, Shigeo; Hashizume, Makoto; Yamaguchi, Shigeki; Eguchi, Susumu; Wada, Norihito; Takiguchi, Shuji; Ieiri, Satoshi; Endo, Shunsuke; et al.
Abstract: In Japan, the first endoscopic surgery, a laparoscopic cholecystectomy, was performed in 1990. Since then, the operative procedure has been standardized, and the safety and usefulness of endoscopic surgery have been evaluated. In accordance with the social acceptance of endoscopic surgery as a less‐invasive surgery, the number of endoscopic procedures has been increasing in all surgical domains. The Japan Society for Endoscopic Surgery (JSES) has played an important role in the development of endoscopic surgery in Japan. For example, JSES established a technical skills certification system for surgeons to train instructors how to teach safe endoscopic surgery, and the organization performs a national survey every 2 years. In 2015, a total of 211 953 patients underwent endoscopic surgery in all surgical domains, including abdominal, thoracic, mammary and thyroid gland, cardiovascular, obstetrics and gynecology, urologic, orthopedic, and plastic surgery. The course of laparoscopic surgery's development and its current status are reported here based on the results of the most recent questionnaire survey conducted by JSES.